2021
DOI: 10.1111/jocn.16080
|View full text |Cite
|
Sign up to set email alerts
|

Full title: The prevalence of and predictors for perioperative hypothermia in postanaesthesia care unit

Abstract: Background: Hypothermia is a common clinical issue during the perioperative period.The patients with perioperative inadvertent hypothermia are associated with higher risk of postoperative complications and higher hospitalisation costs. Aims:The aim of this study is to explore the prevalence of and predictors for hypothermia in patients entering postanaesthesia care unit. Design: Retrospective cohort study.Methods: A rigorous retrospective cohort study was conducted according to the STROBE reporting checklist. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 51 publications
4
7
0
Order By: Relevance
“…Therefore, we paid closer attention to these MT populations undergoing relatively major and complicated abdominal, thoracic and spinal surgeries and excluded those patients undergoing endoscopic or superficial surgeries, such as breast and thyroid surgeries. In our study, the incidence of postoperative hypothermia was 25.7% on arrival at the PACU, which was similar to the incidence in one previous study [17].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Therefore, we paid closer attention to these MT populations undergoing relatively major and complicated abdominal, thoracic and spinal surgeries and excluded those patients undergoing endoscopic or superficial surgeries, such as breast and thyroid surgeries. In our study, the incidence of postoperative hypothermia was 25.7% on arrival at the PACU, which was similar to the incidence in one previous study [17].…”
Section: Discussionsupporting
confidence: 90%
“…This retrospective case-control study was approved by the Ethics Committee of Fudan University Shanghai Cancer Center (FUSCC), China (protocol number: 2209260-4), and the requirement for informed consent was also waived by the Ethics Committee of FUSCC. As one previous study suggested [17], the surgery season had a specific effect on postoperative body temperature; therefore, we collected medical information of patients with American Society of Anesthesiologists physical status (ASA) I or II who underwent scheduled surgery in the cold weather (from November 2020 to March 2021) in FUSCC. Patients were excluded if they underwent emergent surgery or if their records of body temperature and shivering in the PACU were missing.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Postoperative hypothermia is defined as a core body temperature below 36 °C and is encountered in postoperative settings depending on the surgery (Fitriani et al, 2021). Postoperative hypothermia is a detrimental condition that develops depending on duration of surgery, type of anesthesia, patient position during the operation, method used for patient warming, and ambient temperature of the operating room and continues for 24 hours after the surgery if it is not controlled (Plessis, 2016;Simegn et al, 2021;Watson, 2018;Zhang et al, 2021). So, each patient undergoing surgery is at risk for hypothermia (Akhtar et al, 2016;Madrid et al, 2016).…”
Section: Postoperative Hypothermia and Shiveringmentioning
confidence: 99%
“…Retraction may also cause injury to the anterior and posterior intercostal joints (Mesbah et al, 2016). Previous reports state that there is a strong relationship between the lateral decubitus position, which is preferred in thoracic surgery, and postoperative hypothermia and that the lateral decubitus position increases hypothermia (Ge et al, 2021; Min et al, 2018; Zhang et al, 2021). Shivering and chills due to postoperative hypothermia also increase the tension and perception of pain in the incision area due to muscle contractions (Lopez, 2018; Sadeh et al, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%